Cell-Free Supernatant of Bacillus Strains can Improve Seed Vigor Index of Corn (Zea mays L.) Under Salinity Stress - Yaghoubian, Iraj; Msimbira, Levini A.; Smith, Donald Lawrence (Frontiers in Sustainable Food Systems, 2022)
Currently, salinity is known as the second biggest challenge in the world after drought and affects all stages of plant growth. The use of environmentally friendly methods such as microorganisms and their derivatives can reduce the destructive effects of salinity stress. A growth chamber experiment was conducted to determine the effects of cell-free supernatant (CFS) from Bacillus strains on germination of corn under salinity stress. Corn seeds were subjected to three salinity levels (0, 100 and 150 mM of NaCl), cell-free supernatant of Bacillus strains (U35, U47, U48, U49 and U50) at two levels of dilution (1:50 and 1:250). All growth traits of corn seed, including germination percentage and rate, fresh and dry weight of radicle and shoot, radicle and shoot lengths as well as seed vigor index were decreased by increasing salinity. The lowest level of the measured traits was obtained under severe salinity conditions (150 mM NaCl). Contrary to salinity, the CFSs of Bacillus strains increased all the growth traits of corn seeds and reduced the negative effects of salinity, especially severe salinity. At the ratios of 1:50 and 1: 250, the best performance was obtained with U35 and U50, respectively; in general, the highest seed vigor index was obtained at the ratio of 1: 250 and as a result of the application of U50. The correlation between all germination traits and seed vigor index was positive and significant; mean germination time was negatively and significantly correlated with the seed vigor index of corn. The results showed that cell-free supernatant use can reduce the negative effects of salinity and improve seed vigor index and increase the ability of plant seedling establishment under saline conditions.